Genetic variants of ZNF746 and the level of plasma Parkin, PINK1, and ZNF746 proteins in patients with Parkinson's disease - Jolanta Dorszewska; Jolanta Florczak-Wyspiańska; Bartosz Słowikowski; Wojciech Owecki; Oliwia Szymanowicz; Ulyana Goutor; Mateusz Dezor; Paweł P. Jagodziński; Wojciech Kozubski (IBRO Neuroscience Reports)
The occurrence of Parkinson's disease (PD) is influenced by a combination of genetic and environmental factors. Genetic variants of PARK2 (PRKN), PARK6 (PINK1), ZNF746, and their protein products are considered parameters related to the occurrence and development of PD. There is an interplay between Parkin, PINK1, and ZNF746 proteins. Inactivation of Parkin or PINK1 proteins results in elevated levels of the neurotoxic ZNF746 protein and loss of dopaminergic neurons. The objective of this study was to investigate the genetic variations in ZNF746 and the levels of Parkin, PINK1, and ZNF746 proteins in both PD patients and controls within the Polish population. The study included 125 controls and 100 PD patients. Genetic variants were analyzed using PCR-HRM and sequencing. The concentration of Parkin, PINK1, and ZNF746 proteins in plasma was determined by ELISA. The presence of three new genetic variants of ZNF746, chr7:149492883 G>A, ch7:149492890 G>A, ch7:149492694 G>A was demonstrated and the occurrence of ZNF746 c.473 G>A and ch7:149492754 A>G (rs191173107) was confirmed in Polish subjects. There was a significant decrease in Parkin concentration (p < 0.05) observed in PD patients when compared to controls. Reduced levels of Parkin were correlated with a significant rise in the concentration of ZNF746 (p < 0.05) in PD patients when compared with controls. PINK1 protein exhibited no notable alterations in concentration, except in patients who carried the heterozygous ZNF746 variant at ch7:149492694 G>A. The study of ZNF746 variants combined with the assessment of levels of Parkin, PINK1, and ZNF746 proteins provides fresh insights into our understanding of PD pathogenesis.